Gearbox Project Evaluation Software Development for ‘MCD’ Course - NAZRI, NURUL NAJIHAH; AZLAN, MOHD AZWIR (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Gearbox frequently called as transmission as it included a set of gear that arrange properly inside a housing. The calculation of gearbox is a common thing among mechanical engineer. Hence, Mechanical Engineering Program in Univeristi Tun Hussein Onn Malaysia (UTHM) provide exposure to mechanical student about design and calculation of a gearbox in a Mechanical Component Design (MCD) course. The report of MCD project is complex and some of lecturer had difficulty to check the analysis in a short period since it involves with a lot of calculation that related with each other. Previous software is only evaluating the gearbox analysis without considering performance and awarding marks. This study aims to develop an Excel-based gearbox project evaluation software that is able to automatically analyse and evaluate performance for project reports in a short period of time. The analysis of gearbox follows the standard from AGMA and ABMA standards and this software capable to evaluate maximum three set of gear. The method that been used to plan and execute the project refer to waterfall methodology where consist of four phases which are literature review, designing the software, implementation and testing. All of the processes have their relation and allow the objective to be achieved. The system is able to automatically generate result once the student form in Excel is filled out and submitted. It is much faster since the awarding marks is display directly where it is beneficial for the lecturer. Only one testing was managed to be make to validate the system results and the result show that this system are able to extract, reading, compare, analyse data and provide the scale rating same as previous results. Throughout the development, this system is successfully built-in user-friendly interface along with the standards that been followed.